Liminal Fictions in Postmodern Culture - Phillips, Thomas. author. aut Link
VII, 201 p.
Keywords: Liminal Fictions in Postmodern Culture examines distinctive literary, musical, and cinematic narratives that seek to inspire critical thought and conduct through provocation. From Gogol's Dead Souls to Salinger's Franny and Zooey , Phillips argues liminal narratives offer an antidote to the modern commodification of the self.